The Coherence Analysis of Students' Analytical Exposition Texts - Mafuroh, Nur Aeni Afiati; Ningrum, Yusnita Sylvia (ELT Forum: Journal of English Language Teaching, 2019)
This study aims to reveal the coherence of 19 analytical exposition texts written by the fourth semester students of English Department of UNNES through analysis of schematic structure, thematic choices, and thematic developments. Coherence is an essential component to create a make-sense text. Thus, it is very important to know the students’ competency in writing a good text. This study applied a qualitative approach. It employed theories of schematic structure based on stages proposed by Gerot and Wignell (1995), thematic choices from Gerot and Wignell (1995) and thematic developments by Eggins (2004). The findings indicated that students preferably used topical Theme (67.79%) and textual Theme (30.42%). In addition, in terms of thematic developments, Theme Reiteration is the commonest pattern applied by the students. Based on the findings, students’ texts were less coherence because there were several texts having an incomplete thesis at the beginning of the paragraph and one text leaving 1 out of 3 stages of exposition text. Furthermore, the over-use of Theme Reiteration might show that the students’ writing skill is low because they could not elaborate their ideas through various methods. In short, the students could be regarded as novice writers. Keywords: analytical exposition; coherence; schematic structure; thematic choices; thematic development